Simultatenous determination of diacetyl and acetoin in traditional turkish butter stored in sheep’s rumen (Karinyagi) - Gokce, R.; Akdogan, A.; Divriklib, U.; Elci, L. (Grasas y Aceites, 2014)
Commercial Karinyagi (traditionally named karin) is made of cows’ milk cream and is produced by filling butter in cleaned sheep’s rumen. The effect of butter storage in sheep’s rumen on the production of diacetyl and acetoin was investigated. These compounds were determined by GC-MS and they are the typical butter flavor commonly found in fermented dairy products. The modified method for the simultaneous extraction of diacetly and acetoin from butter samples was accurate and precise. The recoveries of diacetyl and acetoin were 94.7 and 110.8%, respectively, while the detection limits were 1.83 and 0.51 mg·L-1, respectively. The proposed method was applied for the monitoring of aroma compounds in Karin butter samples during different time intervals. The concentration of acetoin remained stable through 0–50 days while the concentration of diacetyl increased to 33.0 μg·g-1 up to 40 days and remained constant through 40–50 days.